CLINICAL EVALUATION OF INTRAVENOUS PROPOFOL AND DEXMEDETOMIDINE FOR CONTROLLED HYPOTENSION IN ENT SURGERIES - Dr. Matilda Priyadarshini Lakra; Dr. Raka Rani (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND Otorhinolaryngological surgical procedures are prone to copious bleeding. It is essential to achieve a bloodless field during these procedures for better visibility, to minimise the risk of complications, and ensure patient and surgeon comfort. Controlled hypotension required for ENT procedures have been achieved using a variety of medications. This study aims to evaluate the hemodynamic parameters as a reference for evaluating Propofol and Dexmedetomidine for controlled hypotension during ENT procedures. MATERIAL AND METHODS This study included 40 patients aged 18 to 65 of either gender and of ASA Grade I or Grade II, and were scheduled to have elective ENT procedures. The patients were randomised into two groups of 20 individuals each and were assigned to receive • Group P - Propofol 1mg/kg 10 minutes before induction of general anaesthesia followed by infusion at the rate of 2mg/kg/hr. • Group D - Dexmedetomidine 1µg/kg over 10 minutes before induction of general anaesthesia followed by infusion at the rate of 0.5µg/kg/hr. Vital signs (heart rate, systolic blood pressure, diastolic blood pressure, and mean arterial pressure), as well as respiratory rate and oxygen saturation (SpO2), were recorded. Intraoperative bleeding in the surgical field was evaluated using an average category scale, pain was measured using a Visual Analogue Scale (VAS), and clinical recovery was assessed using the - CRS (Clinical Recovery Score). The student’s unpaired ’t’ test was utilised in order to conduct the statistical comparison between the two groups. For hemodynamic variables, the student’s paired ’t’ test was used. RESULTS There was a significant decrease in pulse rate between pre- and post-operative values for both groups (p value <0.0001). When comparing, pulse rate in Group D was significantly lesser than group P (p value <0.0001). Compared to preoperative values, there was a significant drop in both groups’ systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) (p value<0.0001). There was no significant difference in SBP, DBP and MAP between the two groups. There was no significant difference in intraoperative bleeding between the two groups. Recovery score and post-operative analgesia were better in Group D. CONCLUSION While there was no significant difference in hemodynamics and intraoperative bleeding when comparing dexmedetomidine and propofol, dexmedetomidine offers the advantage of better recovery and post-operative analgesia.